Pain and disability : clinical, behavioral, and public policy perspectives - Osterweis, Marian; Kleinman, Arthur; Mechanic, David, 1936- (National Academy Press, 1987)
Evaluating claims based on pain poses problems for the Social Security Administration (SSA) and other disability insurers. This volume covers the epidemiology and physiology of pain; psychosocial contributions to pain and illness behavior; promising ways of assessing and measuring chronic pain and dysfunction; and clinical aspects of prevention.